Caracterización de radiación solar directa y difusa en condiciones climáticas del Valle del Mantaro - Clemente De la Cruz, Wuilber (2020)
The Mantaro Valley is a privileged area where there is a significant presence of solar radiation, however, the data emitted by the stations in the area are not properly organized, it is more, until 2017 that monitors this parameter was the Meteorological Station from Huayao but with obsolete instruments. Because research related to renewable energy, particularly solar energy, arose, there was a need to analyze and characterize solar radiation data, so that these are the inputs for solar system designs, for this purpose a station was acquired High precision actinometric at the National University of the Center of Peru-Huancayo. To achieve the purpose, the equipment was selected and acquired, then installed and put into operation, with this device 518,000 data was obtained during the period July 2018 to June 2019; the same ones that have been treated with the assistance of Excel software. The characterization shows us that the direct average shortwave radiation is 175.7 W / m2 and the maximum reached was 553.3 W / m2, generating a variation of 151.7 W / m2 and 410.3 W / m2, respectively. The diffuse shortwave radiation was 98.2 W / m2 on an annual average and reached a maximum of 297.3 W / m2, with a standard deviation of 52.7 W / m2 and 170.1 W / m2.